Moving Toward an Understanding of Disability in Older U.S. Stroke Survivors. (January 2018) - Brenner, Allison B.; Burke, James F.; Skolarus, Lesli E.
Objectives: We test a comprehensive model of disability in older stroke survivors and determine the relative contribution of neighborhood, economic, psychological, and medical factors to disability.Method: The sample consisted of 728 stroke survivors from the National Health and Aging Trends Study (NHATS), who were 65 years and older living in community settings or residential care. Confirmatory factor analysis and structural equation modeling were used to test relationships between neighborhood, socioeconomic, psychological, and medical factors, and disability.Results: Economic and medical context were associated with disability directly and indirectly through physical impairment. Neighborhood context was associated with disability, but was only marginally statistically significant ( p = .05). The effect of economic and neighborhood factors was small compared with that of medical factors.Discussion: Neighborhood and economic factors account for a portion of the variance in disability among older stroke survivors beyond that of medical factors.